PREPARING BANANA BRAGA FINANCIAL REPORTS USING CLICK EXCEL ACCOUNTING - Dina Nadia Tampessy; Feni Anita Notanubun; Florence Lisa Hattu; Jeclin Huwae; Aliya Magdalena Maskikit (Media Inovasi Pendidikan dan Publikasi, 2023)
This research aims to prepare financial reports for UKM Banana Braga. Financial reports are information provided to users relating to the condition of the company and its purpose is to describe the condition of the company and make decisions. Technological advances continue to develop in line with the company's need for efficiency which is starting to implement all activities carried out using computerized systems. In today's Digital Era, there are still many businesses that still carry out bookkeeping manually. Because there is a lack of information and understanding regarding applications that can be used to prepare financial reports. Microsoft Excel is a form of application that is part of Microsoft Office. Microsoft Excel is usually used for various kinds of data processing. In preparing financial reports, here we use the Click Excel Accounting (CEA) application at UKM Banana Braga where they still do their bookkeeping manually. The transactions that will be used in this application will occur in September 2023. Financial reports are information provided to users relating to the condition of the company and its purpose is to describe the condition of the company and make decisions.